A STUDY ON THE TEACHING METHOD USED IN TEACHING ENGLISH TO THE FIRST YEAR STUDENT OF SMK N 1 SRAGEN IN 2010/ 2011 ACADEMIC YEAR - UTAMI, PIPIN PUTRI (2011)
The subject of this descriptive research is the first year of SMK N 1 Sragen in 2010/2011 academic year. The objectives of this study are to describe the teaching method applied by the English teacher in SMK N 1 Sragen and to classify the problems faced by the English teacher in teaching English. The writer uses descriptive qualitative research. The writer gets the data of this research from teaching-learning process, interview with the teacher and students, document, and observation. The method of collecting data is observation, document, and interview. The observation in this research are all of the activities occurred in the class. Documents are all of the written data, and documents such as report, material, handbook, students' worksheet, syllabus, and classroom procedures. Interview in this research are the English teacher and students. The results of the research show that: (1) the teaching methods applied by the English teacher are: Cooperative Language Learning (Coop. LL), Communicative Language Teaching (CLT), and Direct Method (DM), while (2) the problems faced by the English teacher are students' interest is low, background knowledge of the students, and limited time.